Prevalence of concomitant pulmonary tuberculosis in patients with newly diagnosed silicosis in a tertiary care center in South India - Navaneethakrishnan Muthulakshmi; Saravanavasan Rajendran; Kannan Muthuraman Alagappan (Asian Journal of Medical Sciences, 2023)
Background: Long-term exposure to silica dust makes people prone for silicosis which raises the risk of the individual in developing pulmonary tuberculosis (PTB). Silicosis is a progressive lung disease characterize with shortness of breath, cough, fever, and bluish skin, caused due to inhalation of crystalline silica dust found in abundance in sand, rock, and quartz.